In A Mindful Moral Voice: Mindful Compassion, The Ethic of Care and Education - Orr, Deborah (Paideusis, 2014)
This paper argues that Carol Gilligan’s Ethic of Care has strong affinities with the Buddhist concept of karuna (compassion) which, Jay Garfield has argued, is the necessary foundation of rights theory. Its central argument is that both moral compassion and thus rights theory are grounded in the natural compassionate care a mother exercises in order to promote the flourishing of her child without which children, and consequently adult society, would not survive in any form. Wittgenstein’s concept of language-games is brought to bear on Buddhist philosophy to foreground the rootedness of human experience in connection and empathy. This further supports the naturalness of compassionate care, the Ethic of Care and karuna. Finally, mindfulness meditation is proposed as a practice appropriate for the educational context for the development of karuna as a moral resource for personal, civil and professional life.